Solar Drying of Veneer and Minor Forest Produce - Sharma, S. N.; Nath, Prem; Bodoni, S. P.; Jain, P. K. (Indian Forester, 1983)
Packed hed type solar air heaters having total collector area 10.3 m3 in 11 m length have been found to yield maximum outlet air tempentures between 90°C and 105°C during April to June at Dehra Dun at air mass flow rates between 2.77 and 5.54 kg/min. Average journal solar collection efficiencies varied between 45.5 and 62%. It is established that temperatures suitable for accelerate drying of veneer, sheet materials, wood wool and minor forest produce on a cottage or small scale can be easily and cheaply achieved by these solar air healers. A 10.3 m2 collector area has been estimated to sulie for a charge capacity of 51 m3 of 2 m n thick green veneer (chargetime 3½ hrs), somewhat more than 28 kg of sal seed (charge time 6½ hrs), and more than 900, 10-leaf bundles (charge 6½ hrs). Possibilities of supplemental solar heating of existing steam heated dryers by this system also exist.